Geech: onomatopoeia and cognition in Central Quechua - Rocha-Martínez, Rolando (2020)
A set of onomatopoeic forms occurring in central Quechua are analyzed, in which, contrary to the traditional structural consideration, bespeak a consistent systematic organization, which is explained by traceable mechanisms of onomatopoeic conformation such as reduplication and vowel quantity. In this context, the main objective is to develop a job of real data collection in order to evaluate the behavior of the conformation of the onomatopoeias through the measurement of acoustic correlates, Such as quantity. Conceptual configurations are detected, in which certain vowel and consonant sequences are linked to a conceptual framework that expresses the way in which Quechua speakers categorize animal emissions. In this last aspect, it should be stated that it is not a matter of repetitions or imitations of animals,but of categorizations in which the association between sound and meaning is expressed in specific phonological-conceptual patterns.